Adsorption of Cr(VI) onto Activated Carbons Prepared from Indigenous Materials - G. Karthikeyan; S. Siva Ilango (E-Journal of Chemistry)
The adsorption of chromium(VI) on activated carbons prepared from low cost materials has been studied by batch process. The influences of various parameters like contact time, dosage, pH, pHzpc and co-ions were experimentally verified. The adsorption of Cr(VI) is maximum at strongly acidic medium (pH 3). Adsorption is explained using Langmuir and Freundlich isotherms with help of chi-square analysis. Thermodynamic parameters like ΔG°, ΔH° and ΔS° were calculated to understand the nature of adsorption. The surface morphology of the three activated carbons before and after metal sorption was verified using scanning electron microscope (SEM) and X-ray diffraction studies (XRD).